Do copepods inhabit hypersaline waters worldwide？ A short review and discussion - Anufriieva, Elena V. (Chinese journal of oceanology and limnology, 2015)
A small number of copepod species have adapted to an existence in the extreme habitat of hypersaline water. 13 copepod species have been recorded in the hypersaline waters of Crimea （the largest peninsula in the Black Sea with over 50 hypersaline lakes）. Summarizing our own and literal_re data, the author concludes that the Crimean extreme environment is not an exception： copepod species dwell in hypersaline waters worldwide. There are at least 26 copepod species around the world living at salinity above 100; among them 12 species are found at salinity higher than 200. In the Crimea Cletocamptus retrogressus is found at salinity 360×10^-3 （with a density of 1 320 individuals/m^3） and Arctodiaptomus salinus at salinity 300×10^-3 （with a density of 343 individuals/m^3）. Those species are probably the most halotolerant copepod species in the world. High halotolerance of osmoconforming copepods may be explained by exoosmolyte consumption, mainly with food. High tolerance to many factors in adults, availability of resting stages, and an opportunity of long-distance transportation of resting stages by birds and/or winds are responsible for the wide geographic distribution of these halophilic copepods.